10.00 An obvious, deceptive, case of immunosuppression. Issue 12 (14th November 2019) - Kumar, Guru; Bodi, Istvan; Flores, Lorena
Abstract : A 69 year old man developed two month progressive short term memory difficulty and then presented with vomiting and confusion. He had bilateral lung transplants for bronchiectasis, immunosuppressed with tacrolimus and mycophenolate for two years. Examination revealed dry thoracic shingles. MRI demonstrated two intra-axial frontal lesions with faint peripheral enhancement, diffusion restriction and vasogenic oedema. Additionally, small foci of diffusion restriction were seen in the upper cervical cord and brainstem. Cerebrospinal fluid showed 340/mm3 lymphocytes, protein 1.2 g/L, normal glucose ratio and positive Varicella zoster virus (VZV) PCR. For possible VZV vasculopathy, he received steroids and acyclovir but unfortunately died of multi organ failure approximately two weeks from admission. Post mortem examination demonstrated necrotic frontal lesions with angiodestructive neoplastic B cell proliferation and EBV positivity. An infarct within the upper cervical cord was also seen with arteritis of one of the posterior spinal arteries. There was widespread perivenular inflammatory cell infiltrate. These findings were consistent with lymphomatoid granulomatosis with vasculitic changes; a rare EBV-driven lymphoproliferative disorder that affects the lungs, skin and central nervous system. Aetiology in this case is felt to be secondary to immunosuppression. However, the role of varicella is unclear and the native lungs have not been examined.